An overview on IoT and its impact on marketing - Simões, Dora (2022)
The internet of things (IoT) is attracting increased attention from researchers, practitioners, consumers, and the media, and it is expected to change dramatically the production and consumption of goods and services, as well as the interaction between organizations and their customers. This chapter explores the challenges of IoT for marketing management. The authors present the main concepts associated to the theme based on the extant literature, considering information management, technological and ethical aspects of its adoption by corporations and consumers, and they discuss the expected impacts on different marketing application domains such as product placement, purchasing behavior, storytelling and communication, customer experience and consumer' brand perception, real-time persona development, and product and content development, among others.